AB0517 Does smoking decrease the efficacy of anti-tumour necrosis factor-alpha therapy in patients with ankylosing spondylitis (as)? : a retrospective, case-control study. (23rd January 2014) - Cheng, K.; Bawa, S.
Abstract : Background: Several studies have shown that smoking is associated with a higher disease activity and decreased efficacy of anti-tumour necrosis factor-alpha (anti-TNFα) therapy in patients with rheumatoid arthritis (RA) 1, 2 . This is the first study investigating if the same relationship applies to AS patients. Objectives: To compare the efficacy of anti-TNFα therapy in AS patients between ever-smokers and non-smokers. Methods: We conducted a retrospective study on all patients with AS (n=73) commencing their anti-TNFα therapy at Gartnavel General Hospital, Glasgow. 11 patients were excluded from the study due to incomplete data. A total of 62 patients (59.7% males), mean age of 50.6 (SD±12.4), were stratified into 2 groups; ever-smokers (71.0%) (current smokers and ex-smokers) and non-smokers (29.0%). The primary endpoint was the proportion of patients that changed their anti-TNFα drug due to loss of efficacy (LOE) after 1, 2 and 3 years. Secondary endpoints were the proportion of patients that met the ASsessment in AS (ASAS 20) criteria and ASAS 40 by month 6 and 12 respectively. Results: At baseline, there was no significant difference between ever-smokers and non-smokers in Bath AS Disease Activity Index (BASDAI), Bath AS Functional Index, Erythrocyte Sedimentation Rate (ESR), spinal pain, patient global, physician global, Health Assessment Questionnaire (HAQ), C-reactive protein (CRP) and Body Mass Index. There was no difference in the proportion of patients who changed their anti-TNFα drug due to LOE after 1 year (14.0%, 33.3%, p=0.154). However, this proportion was higher in non-smokers than in ever-smokers after 2 (41.2%, 7.5%, p=0.005) and 3 (47.1%, 15.4%, p=0.02) years. There was no statistical difference in the proportion of patients meeting the ASAS 20 (p=0.66) and ASAS 40 (p=0.14) between ever-smokers and non-smokers. However, the ASAS 20 and 40 criteria do not incorporate ESR, CRP and HAQ scores. Ever-smokers had a larger improvement in ESR after 12 months (67.2% improvement in ever-smokers, 8.0% deterioration in non-smokers, p=0.01). Further analysis showed that current smokers improved significantly more than non-smokers in CRP (89.3%, 33.2%, p=0.04) levels after 12 months. HAQ scores (41.1%, 8.0%, p=0.050) after 6 months and ESR (73.0%, 8.0%, p=0.051) levels after 12 months suggested a more significant improvement in current smokers but these failed to reach significance. Smoking less than 5 pack years (current and ex-smokers inclusive) is a positive predictive factor for BASDAI response after 12 months (p=0.04). Conclusions: This is a pilot study investigating the effect of smoking on the effectiveness of anti-TNFα therapy in patients with AS. In our cohort, unlike RA, smoking was suggestive of a positive response to anti-TNFα therapy in patients with AS at 6 and 12 months. However, a study with a larger sample size is recommended to confirm this association. References: Söderlin MK, Petersson IF, Geborek P. The effect of smoking on response and drug survival in rheumatoid arthritis patients treated with their first anti-TNF drug. Scand J Rheumatol. 2012 Feb;41(1):1-9. Hyrich KL, Watson KD, Silman AJ, Symmons DP. Predictors of response to anti-TNF-alpha therapy among patients with rheumatoid arthritis: results from the British Society for Rheumatology Biologics Register. Rheumatology (Oxford). 2006 Dec;45(12):1558-65. Acknowledgements: Sister Janice France, RGN Samantha Miller, medical student Disclosure of Interest: None Declared